The Impact of the COVID-19 Pandemic on Pediatric Clinical Practice in Wenzhou, China: A Retrospective Study - Zhang, Hui; Guo, Li-Wei; Gao, Yu-Yan; Yao, Hao; Xie, Zuo-Kai; Zhang, Wei-Xi (Frontiers in Pediatrics, 2020)
Abstract Introduction: The COVID-19 pandemic has affected all aspects of life worldwide. The aim of the present study was to review and describe and appreciate the impact of COVID-19 on the pediatric health care system at a pediatric tertiary hospital in Wenzhou. Methods: A retrospective study was conducted at Yuying Children’s Hospital of Wenzhou Medical University, a public pediatric tertiary hospital in Southern Zhejiang Province with all of the major medical specialties of pediatrics. The data regarding the primary diagnosis of patients were extracted from the electronic medical records system of the hospital. Data for outpatients and inpatients treated at the pediatric department were analyzed in the time frame of 22 weeks since the beginning of the pandemic (from December 30, 2019 to June 2, 2020) and compared with data from the same period in 2019. Results: The total number of outpatient cases in the previous 22 weeks of the year declined from 560620 in 2019 to 247030 in 2020, and inpatient cases decreased from 14177 to 7555. This negative trend settled by week 6 and 7 and subsequently approached the 2019 numbers. The most noticeable decrease in the number of cases was observed in children of preschool age. Moreover, the number of weekly visits decreased at the beginning of the epidemic, reached the lowest value during the lockdown period, and recovered after the lockdown. Conclusion: Based on the results of this study, clinical practice in a pediatric department in Wenzhou was substantially affected by the epidemic and measures such as physical distancing and increased personal hygiene, particularly in preschool age children. An understanding of the trends and impacts of the pandemic on pediatric patients and health systems will facilitate better preparation of pediatricians in the future. Keywords：COVID-19; impact; pediatric; clinical practice; retrospective